Barriers to and strategies for early implementation of pharmacy-delivered HIV PrEP services in Kenya: An analysis of routine data - Nakambale, Hilma N.; Roche, Stephanie D.; Mogere, Peter; Omollo, Victor; Kuo, Alexandra P.; Stergachis, Andy; Baeten, Jared M.; Bukusi, Elizabeth; Ngure, Kenneth; Mugambi, Melissa Latigo; Ortblad, Katrina F. (Frontiers in Reproductive Health, 2023)
Background: For individuals who face challenges accessing clinic-based HIV pre-exposure prophylaxis (PrEP), differentiated service delivery models are needed to expand access and reach. During a pilot study testing a novel pharmacy-delivered PrEP model in Kenya, we used routine programmatic data to identify early implementation barriers and actions that providers and study staff took in response to the barriers. Methods: We trained pharmacy providers at five private pharmacies in Kisumu and Kiambu Counties to initiate and continue clients at risk of HIV acquisition on PrEP for a fee of 300 KES per visit ( 3 USD) using a prescribing checklist with remote clinician oversight. Research assistants stationed at the pharmacies completed weekly observation reports of pharmacy-delivered PrEP services using a structured template. We analyzed reports from the first six month of implementation using content analysis and identified multi-level early implementation barriers and actions taken to address these. We then organized the identified barriers and actions according to the Consolidated Framework for Implementation Research (CFIR). Results: From November 2020 to May 2021, research assistants completed 74 observation reports ( 18/pharmacy). During this period, pharmacy providers screened 496 potential PrEP clients, identified 425 as eligible for pharmacy-delivered PrEP services, and initiated 230 (54%) on PrEP; 125 of 197 (63%) clients eligible for PrEP continuation refilled PrEP. We identified the following early implementation barriers to pharmacy-delivered PrEP services (by CFIR domain): high costs to clients (intervention characteristics), client discomfort discussing sexual behaviors and HIV testing with providers (outer setting), provider frustrations that PrEP delivery was time-consuming and disruptive to their workflow (inner setting), and provider hesitancy to deliver PrEP due to concerns about encouraging sexual promiscuity (characteristics of individuals). To help address these, pharmacy providers implemented a self-screening option for HIV risk assessment for prospective PrEP clients, allowed flexible appointment scheduling, and conducted pharmacy PrEP trainings for newly hired staff. Conclusions: Our study provides insight into early barriers to implementing pharmacy-delivered PrEP services in Kenya and potential actions to mitigate these barriers. It also demonstrates how routine programmatic data can be used to understand the early implementation process.